Benign Localized Fibrous Tumor of the Pleura: Report of 25 New Cases - Enon, Serkan; Kilic, Dalokay; Yuksel, Cabir; Kayi Cangir, Ayten; Percinel, Sibel; Sak, Serpil Dizbay; Gungor, Adem; Kavukcu, Sevket; Okten, Ilker (The Thoracic and Cardiovascular Surgeon, 2012)
Objective Benign localized fibrous tumors (BLFT) of the pleura are very rare slow-growing neoplasms that generally have a favorable prognosis. The aim of this manuscript is to evaluate the predictors of outcome with the review of the literature in a series of 25 patients with BLFT.Methods Between January 1985 and November 2009, 25 patients underwent an operation due to BLFT. Of these patients, 14 (56%) were male; mean age was 41.1 (25 to 64) years. All patients underwent thoracotomy. Left thoracotomy approach was used in 16 patients. The mass lesions were totally excised. The histopathological examinations were performed with hematoxylin-eosin and immunohistochemical staining methods.Results Of the patients, 18 (72%) were symptomatic. Symptoms were cough in 36%, shortness of breath in 32%, and chest pain in 20% of the patients. One patient (4%) appeared to have some symptoms (pain and swelling of the joints) associated with pulmonary osteoarthropathy. Seven patients (28%) underwent an operation due to mass lesion detected at routine control visits. None of the patients had a history of exposure to asbestos. Radiological investigations revealed 16 (64%) mass lesions in the left. Of the lesions found on exploration, 5 (20%) were intrapulmonary localized lesion without pedicle and 20 were pedicled. Of the pedicled masses, 5 were connected to parietal pleura and 15 to visceral pleura and all were intrathoracic extrapulmonary localized lesions. Eight (32%) lesions connected to left lower lobe. Additionally, three pedicled lesions were located in the lung fissure. Pedicled lesions were totally excised together with their pedicles. Intraparenchymal mass lesions were resected using wedge resection. The diameter of the resected masses was ranging between 3 and 22 cm (mean: 8.7). Macroscopically, all were encapsulated with a homogeneous cut surface. Intraoperative mortality and morbidity was not observed. The average hospitalization duration for all patients was 8.6 days (5 to 12). The mean follow-up was 33.6 (9 to 142) months with no recurrence.Conclusions Benign localized fibrous tumors are uncommon and treated by surgical means. According to our data obtained from literature review, clinicians should be aware of recurrence possibility even after complete resection of benign localized fibrous tumor and the risk of malign transformation.
Keywords: solitary; fibrous tumor; surgery